An in vivo humanized model to study homing and sequestration of Plasmodium falciparum transmission stages in the bone marrow - Donsante, Samantha; Siciliano, Giulia; Ciardo, Mariagrazia; Palmisano, Biagio; Messina, Valeria; de Turris, Valeria; Farinacci, Giorgia; Serafini, Marta; Silvestrini, Francesco; Corsi, Alessandro; Riminucci, Mara; Alano, Pietro (Frontiers in Cellular and Infection Microbiology, 2023)
Recent evidence suggests that the bone marrow (BM) plays a key role in the diffusion of P. falciparum malaria by providing a “niche” for the maturation of the parasite gametocytes, responsible for human-to-mosquito transmission. Suitable humanized in vivo models to study the mechanisms of the interplay between the parasite and the human BM components are still missing. We report a novel experimental system based on the infusion of immature P. falciparum gametocyte-infected erythrocytes (PfGIEs) into immunocompromised mice carrying chimeric ectopic ossicles whose stromal and bone compartments derive from human osteoprogenitor cells. We demonstrate that PfGIEs home within minutes to the ossicles and reach the extravascular regions, where they are retained in contact with different human BM stromal cell types. Our model represents a powerful tool to study BM function and the interplay essential for parasite transmission in P. falciparum malaria and can be extended to study other infections in which the human BM plays a role.